Publikasi Bentuk Fungsi dan Kategori SintaksisTuturan Masyarakat Manduro sebagai Pendukung Perkembangan Bahasa Anak Usia Dini - Diana Mayasari; Nanda Riski Ardhana (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
Researchers assume that with the publication of the speech is expected to be useful especially for teachers and employees in Manduro Elementary in language development through language transmission. The purpose of this research is to describe the syntactic structure of Manduro public utterance in Manduro Village, Kabuh Subdistrict, Jombang Regency, covering syntactic functions and categories. Qualitative descriptive method used in this research. With the subject of research is the device of Manduro Village. Samples were taken by purposive sampling with the aim of taking the device of each hamlet contained in Manduro Village. The researcher is the main instrument assisted by the Swadesh Morris questionnaire. Triangulation is used as a test of data validity. The researchers used inductive analysis techniques. The results obtained in this study are syntactic functions consisting of subjects, predicates, objects, descriptions and appendices that categorized nouns, verbs, and adjectives and adverbs. Based on the results of the research, the syntactic structure of public utterance of Manduro has a universality with the syntactic structure of Indonesian and Javanese, only the structures used are not structural. This is because the sentence is a nonformal speech. The results of this study are expected to be used as a supporter of early childhood language development in Manduro Elementary School through the role of teachers in language learning by using examples and communication with students outside the lesson with the manduro language. Thus language learning occurs in a natural context so that the language of the community is not increasingly experiencing shifts and extinctions as well as in the teaching of syntax and as a ruler of language rules in Indonesia.